On the Scientific Heritage of B. Šidiškis - Vozbinas, Stanislovas (Problemos, 1986)
The paper deals with some important aspects of the scientific heritage of the musicologist B. Šidiškis. On the basis of the principle of uncertamly B. Sidiškis’ conception of tonic and atonic music is analysed. The article is supplemented with the list of B. Šidiškis’ scientific works.